Effect of plasma geometry on divertor heat flux spreading: MONALISA simulations and experimental results from TCV. (August 2017) - Gallo, A.; Fedorczak, N.; Maurizio, R.; Theiler, C.; Elmore, S.; Labit, B.; Reimerdes, H.; Nespoli, F.; Ghendrih, P.; Eich, T.; ,
Highlights: Divertor heat flux constraints set limit on the minimum heat flux spreading in ITER. Current parameterizations relate the spreading of experimental heat flux profiles to global plasma parameters allowing multi-machine scaling laws. Simulations with a purely diffusive model of SOL transport support the hypothesis that machine-specific magnetic divertor geometry does not impact the heat channel width. Experimental measurements of plasmas with different divertor leg length obtained in TCV show an unexpected effect of divertor geometry on heat flux spreading. Abstract: Safe ITER operations will rely on power spreading to keep the peak heat flux within divertor material constraints. A solid understanding and parameterization of heat flux profiles is therefore mandatory. This paper focuses on the impact of plasma geometry on the power decay length (λ q ) and the spreading factor ( S ). Numerical heat flux profiles, obtained with the simple SOL transport model MONALISA, agree with theoretical predictions for purely diffusive cylindrical plasmas: λ q does not depend on the machine-specific divertor geometry but only on transport parameters and global geometry ( a, R, k ). A dedicated experiment on TCV was designed to further test this assumption inL -mode plasmas with similar control parameters and upstream shape but different divertor leg length ( Zmag = −14, 0, 28 cm). Characterization of OSP q ∥ profiles with Langmuir probes and infrared thermography enlightens unexpected behavior with the divertor leg length: λ q increases, while S shows no clear trend. These findings suggest that the link between heat flux profiles, plasma geometry and transport is currently not fully understood.